Assemblage and relationality in social-ecological systems. Issue 2 (July 2017) - Lejano, Raul P
How does one begin to construct lasting solutions to environmental problems, the lived experiences of which exceed and defy their framing as environmental (or even as problematic)? Situations exhibit an irreducible autonomy often not amenable to strategic intervention. An emerging concept, proposed as an analytical framework for complex systems, is that of the response assemblage, which is the phenomenal convergence of autonomous elements into provisional, revisable wholes. I argue that these proposals provide interesting possibilities for analysis which, at this point, are not yet operational. Furthermore, when these concepts begin to be translated into analysis, we should encounter a number of unavoidable conceptual issues. I describe some tentative analytical strategies that might be useful for assemblage work, such as a hermeneutic approach to describing the relational. With each provisional analytical turn, I describe how these obdurate conceptual questions re-emerge.